2002
DOI: 10.1113/jphysiol.2002.018010
|View full text |Cite
|
Sign up to set email alerts
|

Force enhancement following muscle stretch of electrically stimulated and voluntarily activated human adductor pollicis

Abstract: For electrically stimulated muscles, it has been observed that maximal muscle force during and after stretch is substantially greater than the corresponding isometric force. However, this observation has not been made for human voluntary contractions. We investigated the effects of active muscle stretch on muscle force production for in vivo human adductor pollicis (n= 12) during maximal voluntary contractions and electrically induced contractions. Peak forces during stretch, steady‐state isometric forces foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
191
8
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(234 citation statements)
references
References 37 publications
34
191
8
1
Order By: Relevance
“…For the stimulation condition T ecc /T 0 ranged between 1.4 − 1.8. The lower end of this range is similar to values reported in previous in vivo stimulation studies for the quadriceps (Dudley et al, 1990;Westing et al, 1991) soleus (Pinniger et al, 2000) and adductor pollicis (De Ruiter et al, 2000;Lee and Herzog, 2002). While the upper end is similar to values found in previous in vivo stimulation studies for the first dorsal interosseus (Cook and McDonagh, 1995) and in vitro studies for mouse and frog muscle fibres (Katz, 1939;Délèze, 1961;Edmann, 1988;Lombardi and Piazzesi, 1990;Krylow and Sandercock, 1997).…”
Section: Discussionsupporting
confidence: 77%
“…For the stimulation condition T ecc /T 0 ranged between 1.4 − 1.8. The lower end of this range is similar to values reported in previous in vivo stimulation studies for the quadriceps (Dudley et al, 1990;Westing et al, 1991) soleus (Pinniger et al, 2000) and adductor pollicis (De Ruiter et al, 2000;Lee and Herzog, 2002). While the upper end is similar to values found in previous in vivo stimulation studies for the first dorsal interosseus (Cook and McDonagh, 1995) and in vitro studies for mouse and frog muscle fibres (Katz, 1939;Délèze, 1961;Edmann, 1988;Lombardi and Piazzesi, 1990;Krylow and Sandercock, 1997).…”
Section: Discussionsupporting
confidence: 77%
“…Recent evidence shows that the PEVK segments of titin bind Ca 2C with high affinity (Tatsumi et al 2001), and that increasing Ca 2C concentration enhances force produced by titin at a given sarcomere length (Labeit et al 2003), suggesting a link between Ca 2C -induced activation and force produced by titin. In studies conducted in our laboratory with singlemuscle fibres (Rassier et al 2003;Rassier & Herzog 2004a,b), whole muscles (Herzog & Leonard 2002;Herzog et al 2003) and human muscles (Lee & Herzog 2002), we observed that passive force is increased when activated muscles are stretched along the descending limb of the force-length relationship, when compared with the passive forces following passive stretches or isometric contractions at the corresponding lengths. We refer to this phenomenon as passive force enhancement (Herzog & Leonard 2002;Herzog et al 2003;Rassier et al 2003;Rassier & Herzog 2004a,b).…”
Section: Introductionmentioning
confidence: 99%
“…As in FD, the occurrence of FE initially was linked only to the lower limb and the peak of the LTC (22,23,24). However, new findings indicate that FE is also observed with reasonable stability in the ascending limb of the LCT (39,80,81,82).…”
Section: Theory Of Non-uniformity and Instability Of Sarcomerementioning
confidence: 90%
“…This association is independent of the coupling of new cross bridges actin -myosin that remains after ceased the stimulus (7,17,22,28,33,97).…”
Section: Elastic Components In Parallel Recruitment Theorymentioning
confidence: 92%
See 1 more Smart Citation